1998
DOI: 10.1590/s0066-782x1998000100004
|View full text |Cite
|
Sign up to set email alerts
|

Respostas cardiorrespiratórias durante exercício em portadores de transplante cardíaco. Análise ergoespirométrica comparativa com indivíduos normais

Abstract: The cardiorespiratory performance in GI was significantly lower at peak exercise and similar to GII in the 40W load, showing the HT benefits cardiac patients during usual activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
1
8

Year Published

2000
2000
2009
2009

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 29 publications
1
3
1
8
Order By: Relevance
“…Following cardiac transplantation, patients progress with a reduction of peak VO 2 9-15 of 30-50% [16][17][18][19][20][21][22] . In our study 6,7 , deficits were 32.4% and 25.7% at peak exercise and at the anaerobic threshold, respectively. Marzo et al 18 found a 35% reduction in the absolute values of the anaerobic threshold.…”
supporting
confidence: 50%
See 4 more Smart Citations
“…Following cardiac transplantation, patients progress with a reduction of peak VO 2 9-15 of 30-50% [16][17][18][19][20][21][22] . In our study 6,7 , deficits were 32.4% and 25.7% at peak exercise and at the anaerobic threshold, respectively. Marzo et al 18 found a 35% reduction in the absolute values of the anaerobic threshold.…”
supporting
confidence: 50%
“…Degré et al 23 reported an early and intense accumulation of lactate during exercise, attributed to increased production in active tissues and reduced clearance secondary to decreased blood flow in the liver and other inactive tissues. In our study 7 , VO 2 in light to moderate submaximal exercise (40 watt load) below the anaerobic threshold was 12.34 and 12.38ml/kg/ min, in transplanted and healthy subjects, respectively, without significant differences between these groups. Meyer et al 24 , working with a load of 50 watts, reported a VO 2 of 0.96 ±0.1 and 0.95±0.08 L/min -1 in transplanted and control subjects, respectively.…”
contrasting
confidence: 44%
See 3 more Smart Citations